Determinants of banks' competitiveness in local financial markets - Ryszard Kata (e-Finanse: Financial Internet Quarterly, 2012)
The article presents the analysis of determinants of banks' competitiveness in local financial markets, with respect to local (cooperative) banks and branches of large commercial banks. The paper also evaluates the competitive position of the banks using the synthetic measure of competitive advantage MPK. The article proves that there are considerable differences between the analyzed groups of banks, in terms of their competitiveness and its determining factors (which are banks' assets). The paper also indicates the areas in which particular banks should make changes in their resources and operational strategies in order to improve their competitiveness in local financial markets.
Keywords: G21; D53; 330; banks; local financial market; competitiveness